INOVASI VAKSIN DENGUE: MENINGKATKAN PERLINDUNGAN DAN MENGATASI DEMAM BERDARAH DENGUE DI MASA DEPAN - Ni Made Indriyani Kusuma Riandra; I Gede Peri Arista; Brigita olivia; Imelda Rismayani Gampur (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
This study discusses Dengue Hemorrhagic Fever (DHF), a viral disease caused by the Dengue virus and can cause clinical symptoms such as fever, headache, nausea, vomiting, skin rash, and joint pain. The immunopathogenesis of DHF occurs when the Dengue virus enters the body and infects white blood cells, which can cause excessive inflammation and can lead to organ failure. The Dengue vaccine can provide protection against the Dengue virus and reduce mortality and complications of this disease. The tetravalent, monovalent, and DNA Dengue vaccines are currently being developed and their effectiveness depends on the serotype of the Dengue virus circulating in a particular area. In the future, the development of the Dengue vaccine is expected to provide more optimal protection by improving effectiveness, safety, and reducing production costs. There are several Dengue vaccine candidates being developed, including weakened virus vaccines and nanoparticle vaccines. With the development of more advanced and effective vaccines, it is hoped that the mortality and complications caused by this disease can be maximally overcome.